Perilaku Konsumen di Era Disrupsi: Peran Interaksi Parasosial terhadap Niat Beli Produk Kolaborasi - Dewi Kusuma Astuti; Adhi Prakosa; Arista Natia Afriany (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the factors that influence the intention to purchase local brand shoes, using the Stimulus Organism Response (SOR) framework. The main focus of this study is to examine the influence of parasocial interaction, brand credibility, celebrity congruence, and brand image on the purchasing intentions of Generation Z in DIY. The method used is quantitative research involving 184 respondents, using purposive sampling and data collection using questionnaires. Data analysis was performed using Structural Equation Model (SEM) – Partial Least Square (PLS). The results show that parasocial interaction has a positive but insignificant effect on brand image. Conversely, parasocial interaction has a positive and significant effect on purchase intention. Brand image cannot mediate the relationship between parasocial interaction and purchase intention. Brand credibility has a positive and significant effect on brand image but a negative and insignificant effect on purchase intention. Brand image acts as a significant mediator in the relationship between brand credibility and purchase intention. In addition, celebrity congruence also shows a positive and significant effect on brand image and purchase intention, with brand image functioning as a significant mediator in this relationship. This study provides important insights for the marketing strategies of local shoe brands that use influencer promotion.